El cultivo de la yuca en Colombia - Luna R., J.M. (International Center for Tropical Agriculture, 1991)
Different aspects of cassava cultivation are described, namely agroclimatic description of thermal belts, area, production, yields, production systems on the Atlantic Coast, var., and uses. The socioeconomic, social, and cultural factors limiting cassava production are listed. The objectives of the cassava plant breeding program of the Instituto Colombiano Agropecuario are indicated; 3 research projects are in process: (1) assessment and maintenance of germplasm, (2) obtainment of cassava hybrids from irradiated seed, and (3) obtainment of early maturing materials. To date, var. CMC 9 (Llanera), Manihoica P-11 (CMC 40), Manihoica P-12 (CMC 76), and Manihoica P-13 (HMC 1) have been released. Close cooperation with CIAT has been in the areas of international germplasm exchange, evaluation and selection of improved materials, recommendations of crosses, and reports on data collected in field evaluations. (CIAT)